Calcificación dentaria como indicador del crecimiento prepuberal - Ossa-Salazar, Jorge Alberto; Puerta-Salinas, Alvaro Rodrigo; Cortés-Castaño, Nelson (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The skeletal indicators of maturation have been utilized with the objective to evaluate the moment in which initial growth spurt in a child is being reached, and in this form take advantage of the potential growth and stablish an especific therapy for that time of growth. The mayoriqr of individual studies of prepuberal growth spurt have been made by means of hand and wrist radiographs. This study has for objective the stablishment of a con-elation between tooth calcification and skeletal maturation, especifically between the inferior canine and second pennanentmolarand the middle .fing-er of the light hand. 45 subjects of the San Antonio Maria Claret school, of both sexes and with ages ranging from 8- 15y-ears of age were pooled. Periapical and panoramic radiographs were taken of the inferior canine and second permanent molar and a penapical radiograph of the middle finger of the right hand. The maturation indicator clasification of Hagg- and Taranger and tooth calcification dad fication of Carmen Nolla were used to correlate them. From the correlations found between them it could be condudec4 that when the inferior canine is in stage 9 of Nolla, exists 95.3% of probability that the subject could be in the maturation spurt or at irs peak and when the second permanent molar is in stage 8 of Nolla, exists 96.9% of probability that the subject could be in the maturation spurt or at it s peak. This conclusions could indicate, that tooth calcification maybe managed by the same Lctors that control bone growth and that a periapical radiograph could be a good helping device in the evaluation of the maturation growth spurt.